2020
DOI: 10.1002/uog.21913
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods of measuring angle of progression in prediction of labor outcome

Abstract: Objectives First, to compare the manual sagittal and parasagittal and automated parasagittal methods of measuring the angle of progression (AoP) by transperineal ultrasound during labor, and, second, to develop models for the prediction of time to delivery and need for Cesarean section (CS) for failure to progress (FTP) in a population of patients undergoing induction of labor. Methods This was a prospective observational study of transperineal ultrasound in a cohort of 512 women with a singleton pregnancy und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Among these, the angle of progression (AoP) is one of the most studied 18,[27][28][29][30] . Many studies have demonstrated that the AoP is a reliable and reproducible tool in the assessment of the degree of fetal head engagement in the birth canal [18][19][20][21][22][23][24][25][26][27]31,32 . To the best of our knowledge, TPU has not been used previously for the evaluation of fetuses in breech presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the angle of progression (AoP) is one of the most studied 18,[27][28][29][30] . Many studies have demonstrated that the AoP is a reliable and reproducible tool in the assessment of the degree of fetal head engagement in the birth canal [18][19][20][21][22][23][24][25][26][27]31,32 . To the best of our knowledge, TPU has not been used previously for the evaluation of fetuses in breech presentation.…”
Section: Introductionmentioning
confidence: 99%
“…However, no statistically significant difference was observed between the two methods (area under the receiver operating characteristic curve [AUC], 0.732; 95% confidence interval [CI], 0.614–0.823 vs. 0.714; 95% CI, 0.622–0.805) [ 16 ]. In a comparative research analysis of the inter- and intra-observer reliability, manual psAOP demonstrated superiority over ms-AOP and the failure rate of obtaining images using automated psAOP, measured by ultrasound devices, was highest at 19% (single observer: AUC, 0.97; 95% CI, 0.95–0.98 vs. 0.93; 95% CI, 0.88–0.96 and two observers: AUC, 0.96; 95% CI, 0.93–0.98 vs. 0.74; 95% CI, 0.58–0.84) [ 17 ].…”
Section: Methods Of Aop (Mid-sagittal Vs Para-sagittal)mentioning
confidence: 99%
“…As demonstrated by the aforementioned studies, the presence of various cutoff values for AOP indicates that the progression of labor is influenced by multiple factors. Frick et al [ 17 ] reported that in a model combining maternal height, parity, gestational age, fetal weight, and AOP, the AUC was the highest at 0.8. Thus, to determine an appropriate cutoff value for AOP, further research is warranted to investigate more comprehensive models that incorporate multiple factors and their interactions.…”
Section: The Usefulness Of Aop According To Labor Stagesmentioning
confidence: 99%
“…53 It is possible to get valuable information that could not be obtained in a VE, such as angle of progression (AoP) which is the angle between a line in the midline of the pubic symphysis and a line running tangentially from the anterior edge of the symphysis to the fetal skull evaluated through transperineal ultrasound (►Figure 2); the head progression distance (HPD) which is the shortest distance between the infrapubic line and the leading edge of the fetal skull, also evaluated through transperineal ultrasound; and the head direction (HD) which is the angle between the infrapubic line, perpendicular to the most caudal part of the pubic symphysis, and a line drawn perpendicular to the widest diameter of fetal head, evaluated through abdominal ultrasound. 47,54 The AoP is the most useful measure to predict the success of vaginal delivery, with the manual parasagittal technique being the most reliable, 55 in which the angle is formed between a line drawn along the superior-inferior axis of the pubic bone and a line drawn along the inferior end of the hyperechogenic pelvic bone forming the vertex of the angle with the fetal head.…”
Section: Fetal Wellbeing During the Labormentioning
confidence: 99%